IKKε deficiency inhibits acute lung injury following renal ischemia reperfusion injury - Meng, Chao (Mol Med Rep, 2020)
Renal ischemia reperfusion injury (IRI) after surgery may promote acute lung injury (ALI) by inducing an inflammatory response. However, the underlying molecular mechanism is still unclear. Studies have reported that inhibitor of κB kinase (IKK)ε primarily regulates inflammation and cell proliferation. The present study aimed to investigate the regulatory role of IKKε in ALI in mice, in order to provide an experimental basis for preventing ALI following surgery-induced renal IRI. C57BL/6J wild-type (WT) and IKKε knockout (IKKε(−/−)) mice underwent bilateral renal pedicle occlusion. The plasma creatinine concentration, urea nitrogen level and lung wet-to-dry ratio were measured at baseline, and at 24 and 48 h after declamping. The histological localization and protein levels of inflammatory factors, such as tumor necrosis factor (TNF)-α, interleukin (IL)-1β and IL-10, were analyzed in lung tissues. Subsequently, the interactions between IKKε and components of the nuclear factor (NF)-κB pathway were studied. The results of the present study demonstrated that the IKKε(−/−) groups displayed similar renal function but less pulmonary edema compared with that of the WT groups. The levels of proinflammatory factors in the lungs were significantly upregulated in WT mice compared with those in IKKε(−/−) mice after IRI surgery. The NF-κB pathway components and downstream factors were substantially upregulated in the WT groups after acute ischemic kidney injury, and these effects were significantly inhibited in the IKKε(−/−) groups. Based on these data, the present study hypothesized that IKKε may serve a negative role in kidney-lung crosstalk after renal IRI and may be a novel target for the treatment of patients with renal IRI.